Research ecosystem at IIUM: the way forward for KIRKHS academics - Akhmetova, Elmira (2019)
This presentation discusses the research ecosystem at IIUM and highlights the responsibilities of IIUM Academicians. The presentation is designed to train new KIRKHS staff